Autologous Chondrocyte Implantation: Second-Look Arthroscopy - Mina Y. Girgis MD; James L. Carey MD (SAGE Publishing, 2023)
Background: A known complication following autologous chondrocyte implantation (ACI) for the repair of cartilage defects is graft hypertrophy. Although hypertrophic tissue can sometimes be asymptomatic, it may cause pain, catching, or effusion prompting a debridement operation-the most common cause for reoperation. Indications: Second-look arthroscopy is required for debridement of symptomatic hypertrophic or delaminated tissue. Technique Description: First, the graft is distinguished from the surrounding tissue. Visually, the graft has a lighter white color than the surrounding egg-shell-colored native cartilage. With a probe, it can be appreciated that the graft also has a softer texture than the firmer surrounding cartilage. Once the graft is identified, hypertrophy can be appreciated by the extent of raised margins from the surrounding cartilage. Delamination can also be seen by visualizing separated strands of graft on the surface or separation of the graft at the margins. A probe may then be used to gently assess the extent of the delamination. After diagnosing hypertrophy or delamination, a shaver is used to gently debride the tissue back so that it becomes flush with the surrounding tissue. Special care must be taken as to not over-debride the tissue, as this can subsequently lead to recurrent cartilage defect. Results: Patients are expected to have resolved pain, catching, and clicking sensations as well as resolved graft-associated effusion following this procedure. Discussion/Conclusion: Due to the incidence of symptomatic graft hypertrophy and delamination following ACI, second-look arthroscopy may be necessary to evaluate and possibly treat a cartilage defect following its repair. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.